2018
DOI: 10.1002/biot.201700618
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Economic and Environmental Aspects of Microalgae Biorefinery for Biofuels Production: A Review

Abstract: Microalgae are considered promising feedstock for the production of biofuels and other bioactive compounds, yet there are still challenges on commercial applications of microalgae-based products. This review focuses on the economic analysis, environmental impact, and industrial potential of biofuels production from microalgae. The cost of biofuels production remains higher compared to conventional fuel sources. However, integration of biorefinery pathways with biofuels production for the recovery of value-adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(38 citation statements)
references
References 55 publications
0
35
0
3
Order By: Relevance
“…The potential of direct AD of microalgae biomass was addressed in their research, taking into account the energetic recovery and necessary nutrient recycle for largescale productions. Chia et al [73] discussed the economic potential of biohydrogen and biogas production in Germany and Spain. Two processes were compared: direct AD of microalgae biomass (DAD) and coupled hydrogen and biogas production (CHB).…”
Section: State Of the Art: Tea Of Microalgal Biogasmentioning
confidence: 99%
“…The potential of direct AD of microalgae biomass was addressed in their research, taking into account the energetic recovery and necessary nutrient recycle for largescale productions. Chia et al [73] discussed the economic potential of biohydrogen and biogas production in Germany and Spain. Two processes were compared: direct AD of microalgae biomass (DAD) and coupled hydrogen and biogas production (CHB).…”
Section: State Of the Art: Tea Of Microalgal Biogasmentioning
confidence: 99%
“…The overwhelming hurdle identified to widespread commercial production of microalgae as a bio-feedstock is the cultivation and harvesting strategy employed (Barsanti and Gualtieri 2018;Chia et al 2018;Beal et al 2015). It has been repeatedly concluded that cultivation in photobioreactors is more costly than open raceway ponds in terms of capital investment, but when downstream processing costs are considered, the higher cell densities achievable in photobioreactors are more economically advantageous (Davis et al 2011).…”
Section: Economic Considerationsmentioning
confidence: 99%
“…Moreover, energy recovery (e.g., biogas production) can be carried out through an anaerobic osmotic membrane bioreactor (An-OMBR) which integrates FO with anaerobic treatment by submerging an FO membrane inside the bioreactor. FO processes can be used to concentrate nutrients and harvest algae which is a bioenergy source, where biodiesel can be produced from its lipid extract and bioethanol can be fermented from its carbohydrates [10,11].…”
Section: Introductionmentioning
confidence: 99%